2020
DOI: 10.1155/2020/3691421
|View full text |Cite
|
Sign up to set email alerts
|

Potential Evapotranspiration Reduction and Its Influence on Crop Yield in the North China Plain in 1961–2014

Abstract: Climate change has caused uneven changes in hydrological processes (precipitation and evapotranspiration) on a space-temporal scale, which would influence climate types, eventually impact agricultural production. Based on data from 61 meteorological stations from 1961 to 2014 in the North China Plain (NCP), the spatiotemporal characteristics of climate variables, such as humidity index, precipitation, and potential evapotranspiration (ET0), were analyzed. The sensitivity coefficients and contribution rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…According to the background of global climate warming, this conclusion is consistent with that of Ma [31] on irrigation water demand and its influencing factors in Shandong Province. Dong et al [32] found that the annual average ET 0 of the North China Plain was 1071.37 mm, and the ET 0 decreased over the past 53 years (−12.8 mm/10 a). This study found that, in the Shandong Province over the past 40 years, ET 0 overall showed a significant downward trend.…”
Section: Discussionmentioning
confidence: 99%
“…According to the background of global climate warming, this conclusion is consistent with that of Ma [31] on irrigation water demand and its influencing factors in Shandong Province. Dong et al [32] found that the annual average ET 0 of the North China Plain was 1071.37 mm, and the ET 0 decreased over the past 53 years (−12.8 mm/10 a). This study found that, in the Shandong Province over the past 40 years, ET 0 overall showed a significant downward trend.…”
Section: Discussionmentioning
confidence: 99%
“…Evapotranspiration is in uenced by multiple components, including temperature, wind speed, relative humidity, solar radiation, and land-use change (Van Der Velde et al 2013; Guo et al 2017; Dong et al 2020). Changes in any of these variables can affect the spatiotemporal distribution of evapotranspiration (Irmak et al 2012; Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in evapotranspiration in the face of rising temperatures is known as the "evaporation paradox" (Brutsaert and Parlange 1998). The paradox can be explained by a combination of factors, including the increase in relative humidity (Dong et al 2020), the decrease in wind speed (Zhao et al 2015;Liu et al 2021), the decrease in solar radiation (Guo et al 2017;Ndiaye et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On dry land, evapotranspiration is influenced by soil moisture, rainfall, and groundwater depth [3]. The duration of solar radiation, air temperature, and wind speed also positively affect potential evapotranspiration, while relative humidity negatively affects potential evapotranspiration [4]. Meanwhile, the factors that affect evaporation are temperature differences, irradiation time, wind speed, and rainfall [5] This evapotranspiration can be used to estimate crop water requirements.…”
Section: Introductionmentioning
confidence: 99%